ANALISA ALGORITMA DAN KARAKTERISTIK KECEPATAN KENDARAAN DI RUAS JALAN ARTERI KOTA SURABAYA - Afifah Ajeng; Vicky Agustin; Hendrata Wibisana (Jurnal Teknik Sipil, 2019)
Vehicle speed is one of the parameters used to detect the characteristics of traffic on a road segment. Vehicle speed is a variable that determines the level of road service as well as the value of the comparison between traffic flow and vehicle density on the road section under study. This study aims to develop an appropriate algorithm that can describe the situation on the arterial road Ir. H. Soekarno about the speed of vehicles passing in it. The method used in this study is polynomial regression with vehicle speed as a dependent variable and the measurement time as a independent variable. The model is said to be good and can be represented by looking at the correlation value R2 that is in each calculated model. The results obtained from this study are that the relationship between vehicle speed and measurement time has the best results on the polynomial model level 7 for measurements in the morning and evening with the same polynomial model. This shows that the graph of the velocity of time is not linear but is a polynomial function. From this research, it can be concluded that the Ir.H.Soekarno road section has varied vehicle speed characteristics and the appropriate mathematical model algorithm is the 6th polynomial model with R2 correlation value of 0.88